Rotate-on-Retract Procedural Automation for Robotic-Assisted Percutaneous Coronary Intervention: First Clinical Experience - Arif Al Nooryani; Wael Aboushokka (Case Reports in Cardiology)
The advent of percutaneous coronary intervention (PCI) has dramatically changed the outlook for patients with cardiovascular disease. However, room for improvement and advancement remains in the safety, speed, and efficiency of manually guided PCI. In recent years, the CorPath robotic platform (Corindus Inc., Waltham, MA) has been approved to aid the interventionalist during PCI and other endovascular interventions. Favorable results in several clinical studies suggest that robotic-assisted PCI may further improve patient outcomes while also benefiting the interventionalist through reduced orthopedic strain and less exposure to ionizing radiation. In this report, we communicate our experience with the first-in-human use of a new, optional automation feature that has been added to the platform’s guidance software. This “Rotate-on-Retract” feature is designed to facilitate faster and more precise maneuvering of the guidewire through tortuous vessels by automatically rotating the guidewire whenever it is retracted by the operator. This movement changes the tip’s orientation in preparation for the next advancement. We evaluated this feature in a patient undergoing PCI to treat a severe (90% stenotic), long, diffuse, and calcified lesion of the proximal to mid LAD segments.